The Quarterly Journal of Economics Volume 130 February 2015 Issue 1 - Front Cover (Quarterly Journal of Economics, 2015)
Journal Article The Quarterly Journal of Economics Volume 130 February 2015 Issue 1 - Front Cover Get access The Quarterly Journal of Economics, Volume 130, Issue 1, February 2015, Page i1, https://doi.org/10.1093/qje/qju040 Published: 26 February 2015